The Grammars of Conjunction Agreement in Slovenian. (March 2015) - Marušič, Franc; Nevins, Andrew Ira; Badecker, William
Abstract In this paper we report on the results of five experiments documenting the existence of three distinct grammars of conjunct agreement in Slovenian, found both within and across individuals: agreement with the highest conjunct, agreement with the closest conjunct, or agreement with the Boolean Phrase itself. We show that this variation is constrained and that some of these mechanisms can be blocked and/or forced depending on the properties of the conjuncts. Finally, we offer the suggestion that the presence of intraindividual variation arises because of ambiguous properties of the primary linguistic data.